2013
DOI: 10.1002/hc.21076
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and QSRR Study for a Series of Phosphoramidic Acid Derivatives

Abstract: New phosphoramidic acid derivatives were synthesized by three different methods in the liquid-liquid and liquid-solid systems. The highest yields were obtained when the liquid-solid system was used. Moreover, for these compounds, the retention factor was predicted, using a robust model obtained for a set of phosphoramidic acid derivatives, which were previously synthesized in our laboratory. For these compounds, the retention factor (k ) was determined by means of the high performance liquid chromatography tec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 37 publications
0
12
0
Order By: Relevance
“…In this context, the designs of novel candidates with enhanced pharmacokinetic properties, better activity profiles, and new therapies to combat HIV drug resistance are vital. These stringent requirements have been addressed by using various computational techniques, such as quantitative structure-activity relationships (QSAR) [ 12 , 13 , 14 , 15 ], pharmacophore modelling [ 16 , 17 ], molecular docking [ 15 , 18 , 19 ], molecular dynamics simulation [ 15 , 20 , 21 ], etc. These approaches have generated considerable interest by reducing the time required for preclinical evaluation, clinical trials, as well as costs and resources.…”
Section: Introductionmentioning
confidence: 99%
“…In this context, the designs of novel candidates with enhanced pharmacokinetic properties, better activity profiles, and new therapies to combat HIV drug resistance are vital. These stringent requirements have been addressed by using various computational techniques, such as quantitative structure-activity relationships (QSAR) [ 12 , 13 , 14 , 15 ], pharmacophore modelling [ 16 , 17 ], molecular docking [ 15 , 18 , 19 ], molecular dynamics simulation [ 15 , 20 , 21 ], etc. These approaches have generated considerable interest by reducing the time required for preclinical evaluation, clinical trials, as well as costs and resources.…”
Section: Introductionmentioning
confidence: 99%
“…The studies have shown that the efficiency of corrosion (IE) is closely related to their structures. Their efficiency arises from their capacity to bind (phosphonic acid group) in a monodentate, bidentate, or tridentate manner to a metal surface [ 7 , 16 , 20 , 21 ]. Therefore, they can act both as mineral scale and corrosion inhibitors [ 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Besides the MDs recorded in the literature, experimental values of the descriptors can be applied in the QSRR models [4]. Moreover, different modeling methodologies, such as multiple linear regression (MLR), partial least squares (PLS), generic algorithms (GA), and artificial neural network (ANN), can be applied in order to develop a QSRR model [2,4,5,6,7,8,9,10,11,12,13,14,15,16,17,18,19,20]. Additionally, the QSRR models can be used in combination with the principal component analysis (PCA), when a large number of columns have been used, and the column classification can be achieved [21].…”
Section: Introductionmentioning
confidence: 99%